(untitled) (Devenires, 2003)
This paper comes from the main author’s researches about the relationships between theology and philosophy in the XX century. The subject is located in a central position over the contemporary discussion; it takes the problem of the sacrament in Jean-Luc Marion’s phenomenology as the standing point, but it also dialogues with authors like Heidegger as well as other important critic interlocutors such as Janicaud. This epilogue about the philosophical character of the sacrament is the aftermath, besides the evident theological charge through its ritual and symbolical dimension to account on its meaning, which main content is its trait of donation, a basic category inside the already mentioned philosophical movement useful as a link concept between philosophy and theology. The paper attempts to report the troublesome relationship man-God through donation as a constitutive opening act for the former and the self-donation as an essential manifestation of the latter at the symbolic level of the sacrament that represents.